1987
DOI: 10.1200/jco.1987.5.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic transformation in cutaneous T cell lymphoma: a clinicopathologic entity associated with poor prognosis.

Abstract: The clinical course of cutaneous T cell lymphoma (mycosis fungoides and Sezary syndrome) is generally indolent, but in occasional patients becomes fulminant. We found that biopsies from patients with accelerating disease can reveal cytologic transformation from previously observed small, convoluted lymphocytes to large cells that are similar to cells seen in large-cell lymphoma. The cerebriform nuclei characteristic of malignant T cells can only rarely be identified. Of 150 cutaneous T cell lymphoma patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 26 publications
0
54
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Notwithstanding, in the past 20 years we have regularly seen MF patients with transformation in skin and even lymph node biopsies who after treatment followed an indolent course for many years. This is reflected in the present study, in which 23 of 100 patients, including 19 with LCT in the skin and 4 with LCT in lymph nodes, had an indolent course for 5 to almost 20 years (median, 99 months; range, 60-235 months) after LCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] Notwithstanding, in the past 20 years we have regularly seen MF patients with transformation in skin and even lymph node biopsies who after treatment followed an indolent course for many years. This is reflected in the present study, in which 23 of 100 patients, including 19 with LCT in the skin and 4 with LCT in lymph nodes, had an indolent course for 5 to almost 20 years (median, 99 months; range, 60-235 months) after LCT.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Apart from clinical stage, large cell transformation (LCT) in MF has been associated with an aggressive clinical course and a poor survival. [3][4][5][6][7][8][9][10] Most studies report a median survival between 2 and 36 months (Table 1). Data on prognostic factors within these studies are however inconsistent and often conflicting and are probably related to the small size of the groups studied thus far (12-45 patients; median, 22 patients).…”
Section: Introductionmentioning
confidence: 99%
“…Because all but these two follow-up biopsies had been obtained from patients without evidence of extracutaneous disease at the time of biopsy the clinical stage was determined only by the type of skin lesions, defined as the presence of patches and plaques covering more than 10% of the skin surface (T2) or the presence of tumors (T3). Because previous studies demonstrated unequivocally that skin tumors showing blastic transformation have a significantly worse prognosis than tumors without blastic transformation 23,24 within the T3 category, distinction was made between tumors with and tumors without blastic transformation, defined by the presence of more than 50% blast cells. Therefore, we will refer primarily to the type of skin lesion (patches/plaques, tumors without, and tumors with blastic transformation).…”
Section: Patientsmentioning
confidence: 99%
“…This is probably a closer reflection of the actual rate given the histopathological and clinical biases of earlier reports [8]. Transformation generally portends a grave prognosis, with median survival times reported from 2 to 36 months [4,5,6,7,8,9]. Transformation within 2 years of diagnosis and an advanced clinical stage at the time of transformation add additional negative prognostic indicators [8].…”
Section: Introductionmentioning
confidence: 99%
“…Large cell transformation of MF (T-MF) has been reported to occur in 8–55% of MF patients and can be accompanied by expression of a TNF receptor CD30 or the T cell receptor α-chain, CD25 [4,5,6,7,8]. Diamandidou et al [8] defined large cell transformation as >25% large cells within the lymphocytic infiltrates and reported a transformation rate of 23%.…”
Section: Introductionmentioning
confidence: 99%